Synthesis of Bi2O3–Bi4V2O11 heterojunctions with high interface quality for enhanced visible light photocatalysis in degradation of high-concentration phenol and MO dyes. Issue 18 (17th April 2018) - Liu, Ting; Mao, Yan Ge; Peng, Yin
Abstract : Bi2 O3 –Bi4 V2 O11 heterostructures with high interface quality were synthesized by calcining Bi2 VO5.5 –Bi(OHC2 O4 )·2H2 O precursors. The Bi2 O3 –Bi4 V2 O11 heterostructure exhibits outstanding photocatalytic activity for degrading phenol and MO dyes with high concentration under visible light irradiation. Abstract : One-dimensional Bi2 O3 –Bi4 V2 O11 heterostructures with enhanced visible light photocatalytic performance were synthesized by high temperature calcination of Bi(OHC2 O4 )·2H2 O–Bi2 VO5.5 precursors. The Bi4 V2 O11 nanosheets uniformly grew on the Bi2 O3 porous rods by crystallographic-oriented epitaxial growth, which increased the interface quality and then provided the smallest penetration barrier for electron–hole pair transfer between Bi2 O3 –Bi4 V2 O11 interfaces. The photocatalytic performance of the obtained products was evaluated by degradation of phenol and methyl orange (MO) with high concentration under visible light irradiation. The results show that the Bi2 O3 –Bi4 V2 O11 heterostructure displays higher photocatalytic activity than pure phase Bi2 O3 and Bi4 V2 O11, and more encouragingly, 40 mg L −1 of phenol can be completely degraded in 30 min under visible light irradiation using the Bi2 O3 –Bi4 V2 O11 (DS-2) heterostructure as the photocatalyst. This enhanced photocatalytic performance is ascribed to the synergistic effect of the suitable band alignment of the Bi2 O3 and Bi4 V2 O11, high interface quality and one-dimensionally ordered nanostructure. Radical scavenger experiments indicate that holes (h + ) and superoxide radicals (˙O2 − ) were the main active species for phenol (and MO) degradation during the photocatalytic process. This work would offer a simple route to design and fabricate junction structures with high interface quality for photocatalytic applications.